Warunki do zabawy na Przygodowym Placu Zabaw w Berkeley Marina w Kalifornii - Agnieszka Janik (Problemy Wczesnej Edukacji)
The following publication is an attempt to describe observed reality, especially in terms of conditions provided for play. This article is the result of author’s research visit at the City of Berkeley’s Marina Adventure Playground. During the visit the author had the opportunity to attend the unique and dynamic play environment of adventure playground in Berkeley Marina that enables its users to saw, hammer, build forts, play with water and fire. At the same time the it was designed in the way that encourages to play not only children’s but also adults. The presented content includes: the concept of playground in Berkley, its the design of space and play equipment, its policy and role of play leaders. The research methodology included qualitative procedure. Qualitative analysis, ethnographic observation and qualitative research interview has been used.